Antiprotozoal activity of quinonemethide triterpenes from Maytenus ilicifolia (Celastraceae) - Dos Santos, Vania A. F. F. M. [UNESP]; Leite, Karoline M. [UNESP]; Da Costa Siqueira, Mariana [UNESP]; Regasini, Luis O. [UNESP]; Martinez, Isabel [UNESP]; Nogueira, Camila T. [UNESP]; Galuppo, Mariana Kolos; Stolf, Beatriz S.; Pereira, Ana Maria Soares; Cicarelli, Regina Maria Barreto [UNESP]; Furlan, Maysa [UNESP]; Graminha, Márcia Aparecida Silva [UNESP] (MDPI, 2013)
The present study describes the leishmanicidal and trypanocidal activities of two quinonemethide triterpenes, maytenin (1) and pristimerin (2), isolated from Maytenus ilicifolia root barks (Celastraceae). The compounds were effective against the Trypanosomatidae Leishmania amazonensis and Leishmania chagasi and Trypanosoma cruzi, etiologic agents of leishmaniasis and Chagas' disease, respectively. The quinonemethide triterpenes 1 and 2 exhibited a marked in vitro leishmanicidal activity against promastigotes and amastigotes with 50% inhibitory concentration (IC50) values of less than 0.88 nM. Both compounds showed IC50 lower than 0.3 nM against Trypanosoma cruzi epimastigotes. The selectivity indexes (SI) based on BALB/c macrophages for L. amazonensis and L. chagasi were 243.65 and 46.61 for (1) and 193.63 and 23.85 for (2) indicating that both compounds presented high selectivity for Leishmania sp. The data here presented suggests that these compounds should be considered in the development of new and more potent drugs for the treatment of leishmaniasis and Chagas' disease. © 2013 by the authors.
Keywords: Celastraceae; Leishmanicidal; Maytenin; Maytenus ilicifolia; Pristimerin; Quinone-methide triterpenes; Trypanocidal; antitrypanosomal agent; plant extract; quinone derivative; triterpene; animal; Bagg albino mouse; cell culture; chemistry; drug effect; IC 50; LD 50; Leishmania; macrophage; Maytenus; mouse; parasitology; physiology; plant root; Trypanosoma cruzi; Animals; Cells, Cultured; Inhibitory Concentration 50; Lethal Dose 50; Macrophages; Mice; Mice, Inbred BALB C; Plant Extracts; Plant Roots; Quinones; Triterpenes; Trypanocidal Agents